2020
DOI: 10.1542/peds.2019-1655
|View full text |Cite
|
Sign up to set email alerts
|

Global Health Experience and Interest: Results From the AAP Periodic Survey

Abstract: BACKGROUND: Interest and participation in global health (GH) experiences have increased over the past 30 years in both medical schools and residencies, but little is known at the level of practicing pediatricians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…12 In the second, a survey of practicing pediatricians in 2017, 32% reported plans to work in a low-or middle-income country and 5.1% reported overseas global health experiences in the previous 12 months. 16 Respondents' interest in working in global health remained largely constant from before to after track participation, likely reflecting their self-selection into a global health track, similar to the conclusion of the study by Gupta et al 11 of Yale internal medicine residents. However, respondents reported that their specific interests were influenced by participation in the track, including sub-specialty choice, increased interest in global research and public health, as well as working with immigrant and refugee populations.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…12 In the second, a survey of practicing pediatricians in 2017, 32% reported plans to work in a low-or middle-income country and 5.1% reported overseas global health experiences in the previous 12 months. 16 Respondents' interest in working in global health remained largely constant from before to after track participation, likely reflecting their self-selection into a global health track, similar to the conclusion of the study by Gupta et al 11 of Yale internal medicine residents. However, respondents reported that their specific interests were influenced by participation in the track, including sub-specialty choice, increased interest in global research and public health, as well as working with immigrant and refugee populations.…”
Section: Discussionsupporting
confidence: 65%
“… 12 In the second, a survey of practicing pediatricians in 2017, 32% reported plans to work in a low- or middle-income country and 5.1% reported overseas global health experiences in the previous 12 months. 16 …”
Section: Discussionmentioning
confidence: 99%
“…These data are consistent with pediatric resident exposure 23 and 2017 AAP-PS data. 24 Extrapolating our data to the full workforce of board-certified pediatricians (74 490 as of December 2017 25 ), our findings suggest that upwards of 25 000 pediatricians have international experience and nearly 9000 have spent professional time abroad in the last 5 years. These pediatricians are traveling to regions of the world where there may be fewer than 1 physician per 1000 patients and significantly lower numbers of pediatricians; this type of travel, if wellcoordinated, could potentially address gaps in care in those regions.…”
Section: Discussionmentioning
confidence: 73%
“…Participation in global health engagements in low-and middle-income countries (LMICs) has become well within reach for anyone with the interest and means to pursue it (Schnable, 2021). Organizations of diverse variety have offered opportunities for individuals from high-income countries (HICs) to travel to LMICs to take part in global health activities, including clinical service, health education, and other health-focused service activities (Chan, Sisk, Yun, & St Clair, 2020;Kerry et al, 2011;Lasker, 2016;Oliphant, 2018;Sullivan, 2018). Universities, nonprofits, religious institutions, and even for-profit volunteer placement companies have offered interested individuals the opportunity to "give back" and "do good" in countries perceived to be in need of such services (Lasker, 2016).…”
Section: Introductionmentioning
confidence: 99%